Redactions and dates of the compilation of the Čingiz-nāmä of Ötämiš Ḥāǰǰī - Göncöl Cs. (Золотоордынское обозрение, 2023)
This article aims to scrutinise the relationship between the texts of the 16-th century chronicle, the so called Čingiz-nāmä of Ötämiš Ḥāǰǰī, preserved in two manuscripts, as well as to determine the date(s) of the compilation of the work. Materials: The Tashkent and Istanbul manuscripts of the Čingiz-nāmä of Ötämiš Ḥāǰǰī, Central Asian chronicles in Turkic and Persian, relevant scholarly literature. Results and novelty of the research: Analysing the relationship of the two texts, the author has come to the conclusion that the Tashkent and Istanbul manuscripts of the above-mentioned chronicle contain different redactions of the Čingiz-nāmä written by the same chronicler. Furthermore, the author argues that the text preserved in the Tashkent manuscript is the initial redaction compiled before the year 1539, while the text of the Istanbul manuscript contains the second redaction – an extended one – written around middle of the 1540s.